Spin filtering of a termination-controlled LSMO/Alq3 heterojunction for an organic spin valve. Issue 35 (29th August 2017) - Lam, Tu-Ngoc; Huang, Yen-Lin; Weng, Ke-Chuan; Lai, Yu-Ling; Lin, Ming-Wei; Chu, Ying-Hao; Lin, Hong-Ji; Kaun, Chao-Cheng; Wei, Der-Hsin; Tseng, Yuan-Chieh; Hsu, Yao-Jane
Abstract : La1− x Sr x MnO3 (LSMO) is well known as an efficient spin-injection electrode in ferromagnetic–organic hybrid-based organic spin valves (OSV). Abstract : La1− x Sr x MnO3 (LSMO) is well known as an efficient spin-injection electrode in ferromagnetic–organic hybrid-based organic spin valves (OSV). Herein, we examine the influence of three terminating layers of LSMO films (mixed-, MnO2 -, and LaSrO- (LSO-) terminated) on the spin filter at the bottom interface of tri (8-hydroxyquinoline) aluminum (Alq3 ) deposited on these substrates. Angle-dependent X-ray photoelectron spectra (XPS) demonstrated the presence of SrO segregation at the outermost layer for three types of LSMO films but in different amounts that might contribute to their magnetic properties. A weak surface coupling between LSMO and Alq3 was obtained through a small increase of Mn L-edge X-ray magnetic circular dichroism (XMCD) but it does not vary the bulk magnetic properties of LSMO films upon Alq3 adsorption (LSMO/Alq3 ). The surface dipoles due to the interaction between LSMO films and Alq3 were found to be 0.5, 0.5, and 0.7 eV for the mixed-ter/Alq3, MnO2 -ter/Alq3, and LSO-ter/Alq3 interfaces, respectively. Our results indicate that the segregated SrO layer plays an important role in the surface electronic and magnetic properties at LSMO/Alq3 interfaces, which contributes to a fundamental understanding of the spin injection and transport in LSMO-Alq3 hybrid-based OSV devices.